Effects of statins on male reproductive health: a systematic review of rodent studies and their potential implications to human male reproduction - Leite, Gabriel Adan Araújo; Lazzari, Virgínia Meneghini; Simão, Vinícius Augusto [UNESP]; Sanabria, Marciana (Taylor & Francis, 2025)
Statins are the drugs recommended for the treatment of dyslipidemia and for preventing cardiovascular risks in humans. However, it is reported that statins may impair reproductive parameters in males at different periods of exposure in pre-clinical studies. This work carried out a systematic review of the literature concerning the primary studies that evaluated the reproductive outcomes in male rats and mice exposed to several statins available on the market. The literature search was performed employing several databases, including Embase, Web of Science, PubMed, LILACS, Scopus, and SciELO, by using different combinations of the search terms "statins," "mice," "rats," "male reproduction," "fertility" and "sperm," followed by the Boolean operators AND or OR. Then, duplicated articles or studies that did not meet the eligibility criteria were excluded. Posteriorly, the risk of bias was assessed following the essential ten points of the ARRIVE guidelines. Afterward, the extraction and qualitative analysis of the data were performed, and when possible, a meta-analysis was carried out. The results indicated that normolipidemic healthy rodents exposed to statins showed reproductive impairment, such as reduced sperm quality, diminished testosterone production, and delayed puberty onset. Additionally, in vitro and ex vivo studies demonstrated a decrease in testosterone synthesis after statin exposure. However, when rodents were induced to diabetes and erectile dysfunction or were fed a high-fat diet, these diseased animals exposed to statins exhibited improved erectile function, increased sperm quality, and no changes or augmented testosterone levels. Given the reproductive toxicity generated by statin exposure in healthy male rodents without any previous dysfunction, these drugs should be reserved for treating dyslipidemia or, when appropriate, as an adjunct therapy for erectile dysfunction.